2016
DOI: 10.1097/md.0000000000002496
|View full text |Cite
|
Sign up to set email alerts
|

Fbxw7 Tumor Suppressor

Abstract: Rapidly accumulating data indicate that F-box/WD repeat-containing protein 7 (Fbxw7) is one of the most frequently mutated genes in human cancers and regulates a network of crucial oncoproteins. These studies have generated important new insights into tumorigenesis and may soon enable therapies targeting the Fbxw7 pathway.We searched PubMed, Embase, and ISI Web of Science databases (1973–2015, especially recent 5 years) for articles published in the English language using the key words “Fbxw7,” “Fbw7,” “hCDC4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 101 publications
0
38
0
Order By: Relevance
“…FBXW7 mutations are uncommon in lung cancer, according to COSMIC. FBXW7 is implicated in proteasome degradation of specific substrates and control tumorigenesis, acting on cell cycle, differentiation and apoptosis [37]. It is also involved in epithelial-to-mesenchymal transition by controlling mTOR pathway [38].…”
Section: Discussionmentioning
confidence: 99%
“…FBXW7 mutations are uncommon in lung cancer, according to COSMIC. FBXW7 is implicated in proteasome degradation of specific substrates and control tumorigenesis, acting on cell cycle, differentiation and apoptosis [37]. It is also involved in epithelial-to-mesenchymal transition by controlling mTOR pathway [38].…”
Section: Discussionmentioning
confidence: 99%
“…The FBXW7 gene, which encodes FBW7, is frequently mutated in diverse cancer types including leukemia and breast, colon, liver, ovarian, and lung cancers [26][27][28] . FBW7 expression is transcriptionally regulated by the tumor suppressor p53 29 , and loss-of-function of p53 reduces the expression of FBW7 30 . Therefore, the tumor-suppressive function of FBW7 may be considered only in the context of p53.…”
mentioning
confidence: 99%
“…With a mutation rate of 6% to 35%, it is considered to be the most common tumor suppressor right behind p53 and PTEN 7. In addition, many upstream molecules, such as transcriptional factors, kinases and microRNA, can also regulate FBW7 either transcriptionally or post‐translationally 24.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation is tightly associated with the cell cycle, which is rigidly regulated by a series of kinases, among which Cyclin E and Aurora B are 2 important FBW7 substrates involved in the promotion of G1/S and G2/M transition, respectively 5, 8, 21. Previous studies have implicated the role of FBW7 in the regulation of cell proliferation in colon, breast and kidney cancers 7. In our study, we found that forced FBW7 expression inhibited the proliferation of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation